Continuous theta burst stimulation over left supplementary motor area facilitates auditory-vocal integration in individuals with Parkinson’s disease - Dai, Guangyan; Wang, Meng; Li, Yongxue; Guo, Zhiqiang; Jones, Jeffery A.; Li, Tingni; Chang, Yichen; Wang, Emily Q.; Chen, Ling; Liu, Peng; Chen, Xi; Liu, Hanjun (Frontiers in Aging Neuroscience, 2022)
Accumulating evidence suggests that impairment in auditory-vocal integration characterized by abnormally enhanced vocal compensations for auditory feedback perturbations contribute to hypokinetic dysarthria in Parkinson’s disease (PD). However, treatment of this abnormality remains a challenge. The present study examined whether abnormalities in auditory-motor integration for vocal pitch regulation in PD can be modulated by neuronavigated continuous theta burst stimulation (c-TBS) over the left supplementary motor area (SMA). After receiving active or sham c-TBS over left SMA, 16 individuals with PD vocalized vowel sounds while hearing their own voice unexpectedly pitch-shifted two semitones upwards or downwards. A group of pairwise-matched healthy participants were recruited as controls. Their vocal responses and event-related potentials (ERPs) were measured and compared across the conditions. The results showed that applying c-TBS over left SMA led to smaller vocal responses paralleled by smaller P1 and P2 responses and larger N1 responses in individuals with PD. Major neural generators of reduced P2 responses were located in the right inferior and medial frontal gyrus, pre- and post-central gyrus, and insula. Moreover, suppressed vocal compensations were predicted by reduced P2 amplitudes and enhanced N1 amplitudes. Notably, abnormally enhanced vocal and P2 responses in individuals with PD were normalized by c-TBS over left SMA when compared to healthy controls. Our results provide the first causal evidence that abnormalities in auditory-motor control of vocal pitch production in PD can be modulated by c-TBS over left SMA, suggesting that it may be a promising non-invasive treatment of speech motor disorders in PD.